Financial Reporting Preparer’s Satisfaction and Intention to Switch to XBRL reporting: A Model (Journal of Entrepreneurship and Business, 2022)
The objective of this paper is to develop a conceptual framework for understanding financial reporting preparers’ satisfaction and intention to switch from conventional to XBRL reporting. Based on the review and synthesis of relevant literature from prior XBRL adoption research, technology usage behavior, and the user satisfaction element in information system studies, gaps have been identified and a conceptual framework has been developed. This framework includes eight constructs, i.e., perceived ease of use, perceived usefulness, perceived compatibility, information quality, service quality, system quality, preparer’s satisfaction, and the intention to switch to XBRL reporting. The framework can be used to conduct research and establish appropriate XBRL plans. Furthermore, by leveraging the benefits of XBRL, this framework will assist decision-makers in formulating strategies. Nevertheless, this study is limited to identifying gaps and to suggesting new conceptual frameworks based on previous literature and empirical studies. Thus, this paper implies that further empirical research be conducted to validate the suggested integrated model.
Keywords: Array; Array; Array; Array; Array; Array